Sexual abuse of girl children Some hidden facts - Rama Achyut Pande (New Delhi Rawat Publications, 2016)
Society is grappling with many problems, one of the more serious problems is girl-child sexual abuse. In India, the issue of girl-child sexual abuse is kept veiled and socially unspeakable. Even though some studies have shown its prevalence in India, social stigma, traditions, and cultural barriers have always kept this issue in the dark. Owing to a restrictive social upbringing, abused girls do not seek help from family or from the outside. The socialization process teaches the girls to not respond, rather to bear, adjust, and suffer in silence. This book is an attempt to break this silence of the abused girl children. Drawing upon the research conducted in the Beed district of Maharashtra, the book portrays the severity of the physical, emotional, and psychological pain of the sexually abused girl-children. This book will be useful to parents, social workers, teachers, students, women studies researchers, and all the NGOs working on this issue. Moreover, this book will help policy-makers and the government as they strive to create strategies and rehabilitative programs. [Subject:?Criminology, Gender Studies.
Keywords: Social problems